Comparative Study of Hearing Status after Modified Radical Mastoidectomy with and Without Reconstruction - Islam, Syed Sanaul; Siddiquee, Belayat Hossain; Kabir, ABM Luthful; Islam, Muhammad Rafiqul; Razzak, Md Abdur (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To compare the hearing status after modified radical mastoidectomy with and without reconstruction. Materials and Methods: This was a cross sectional observational study which was carried out in the departments of Otolaryngology and Head-Neck surgery of Bangabondhu Sheikh Mujib Medical University Dhaka Medical College during the period of April’2012 to September ’2012. A Total 30 patients of CSOM (Atico-antral variety) underwent modified radical mastoidectomy (MRM) with or without reconstruction were included in this study. Patients were divided into two groups according to operative procedure. Patient underwent MRM without reconstruction belonged to group I (n=15) and with reconstruction was considered as group II(n=15). Patients were examined thoroughly and preoperative hearing level was assessed by pure tone audiometry one week before operation. Both groups of patients were operated by general anesthesia under microscope with post auricular approach. In group II, temporalis fascia and cartilage were taken as graft materials after doing modified radical mastoidectomy. Post operative patients were followed up at regular intervals. Pure tone audiogram (PTA) was done after 8 weeks and hearing assessment was compared by closure of air bone gap. Results: In this study majority of patients were within 11-20 years and most of patients were male. Closure of air-bone gap was higher in patients underwent MRM with reconstruction. Conclusion: Reconstruction following MRM causes better hearing gain and also improves the quality of life. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 41-46